Pikovaya dama opera in three acts, seven scenes = Pique dame = The queen of spades - Čajkovskij, Pëtr Ilʹič 1840-1893 (TDK, 2007)
Tchaikovsky's opera about a man's desire to learn the secret of the three enchanted cards that will allow him to always win at the gaming tables